Pemanfaatan Fotografi Produk Berbasis Website Sebagai Media Promosi Pada UMKM Ovie Cake Semarang - Lia Handayani; Ayyub Hamdanu Budi Nurmana MS; Muhammad Sholikhan (UNIVERSITAS STEKOM, 2025)
Digital technologies have been developed very fast, and as a result, we have seen a big change in the way companies are marketing their products, especially in the case of Micro, Small, and Medium Enterprises (MSMEs). Ovie Cake, a local MSME in Semarang, is experiencing difficulties in seeking market expansion because the product photos on its social media have been fluctuating; thus, the engagement has dropped. The objective of this research is to find out the most applicable product photography methods and put together a promotional medium based on the website. The study utilized various methods such as an observation method, social media analysis, a photography experiment, and catalog-based website development. For photography, they picked still life combined with the 45-degree angle and high-key lighting. Properly lit product photos attract consumers’ attention and show the professionalism of the brand. The website, attracting users without borders, became a successful digital promotion platform to open new markets.